ANALISIS HUBUNGAN ANTARA GHRMPS,CORPORATE SOCIAL RESPONCIBILTY, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, DAN ENVIROMENTAL MANAGEMENT SYSTEM DI PT. GOJEK INDONESIA - Muhammad Dimas Pangestu; Zamzam Nurul Haj; Netania Emilisa; Bagas Prawiro Sastro (Peneliti.net, 2023)
Sustainability is crucial if organizations are to solve ecological issues on a global scale. Economic success and individual well-being are impacted by how well we can manage the environment. This journal was created with the intention of examining the connections between GHRMP and OCBE, GHRMP and EMS, and the indirect impacts of OCBE from PT. Indonesian GoJek. The research is conducted using a quantitative survey methodology. The dependent variables in this study include organizational citizenship behavior for the environment, the environmental management system, and corporate social responsibility. The independent variable is green human resource management practice. utilizing the purposive sample technique, literature, and distribution of questionnaires. and evaluated the reliability and validity. The results of the current study suggest that manufacturing businesses should embrace EMS ISO14001, promote OCBE, and employ GHRMP effectively to improve CSR. Utilizing these green strategies will lessen the performance gap between the economy and the environment. In order to promote and motivate staff members to participate in OCBE and environmental efforts, such as EMS ISO14001, managers must have a thorough understanding of GHRMP.